Isometric thumb extension exercise as part of a multimodal intervention for de Quervain's syndrome: A randomised feasibility trial. (June 2023) - McBain, Brodwen; Rio, Ebonie; Cook, Jill; Sanderson, Jeffrey; Docking, Sean
Introduction: de Quervain's syndrome is a painful condition commonly presented to hand therapists. Exercise is utilised as an intervention, but isometric exercise has not been investigated. We aimed to assess the feasibility and safety of isometric thumb extension exercise for de Quervain's syndrome and to explore differences between high-load and low-load isometric exercise. Methods: This parallel-group randomised clinical feasibility trial included individuals with de Quervain's syndrome. All participants underwent a 2 week washout period where they received an orthosis, education, and range of motion exercises. Eligible participants were then randomised to receive high or low-load isometric thumb extension exercises, performed daily for 4 weeks. Feasibility and safety were assessed by recruitment and drop-out rates, adherence, adverse events, and participant feedback via semi-structured interviews. Secondary outcomes included patient-reported outcomes for pain and function, and blinded assessment of range of motion and strength. Results: Twenty-eight participants were randomised. There were no drop-outs after randomisation, and no serious adverse events. Adherence to exercise was 86.7%, with 84% of participants stating they would choose to participate again. There were clinically and statistically significant improvements in pain and function over time ( p < 0.001) but not in range of motion or strength. There were no statistically significant between-group differences. Conclusions: Isometric thumb extension exercise within a multimodal approach appears a safe and feasible intervention for people with de Quervain's syndrome. A large multi-centre trial would be required to compare high- and low-load isometric exercises. Further research investigating exercise and multimodal interventions in this population is warranted.